2013
DOI: 10.1111/all.12130
|View full text |Cite
|
Sign up to set email alerts
|

Dog saliva – an important source of dog allergens

Abstract: BackgroundAllergy to dog (Canis familiaris) is a worldwide common cause of asthma and allergic rhinitis. However, dander extract in routine diagnostics is not an optimal predictor of IgE-mediated dog allergy. Our objective was to evaluate saliva as an allergen source for improved diagnostics of allergy to dog.MethodsIgE-binding proteins in dog saliva and dander extract were analysed by immunoblot and mass spectrometry (LC-MS/MS) using pooled or individual sera from dog-allergic patients (n = 13). Sera from 59 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…SIT for pets is highly efficient and secure despite polysensitization and polyallergy. As for Canf1 for dog allergy [8], Feld1 alone seems not sufficient for diagnosis and consecutively treating cat allergic patient. + T cells in all allergic manifestations, however, largest numbers were detected upon stimulation with house dust mite & grass pollen extracts.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…SIT for pets is highly efficient and secure despite polysensitization and polyallergy. As for Canf1 for dog allergy [8], Feld1 alone seems not sufficient for diagnosis and consecutively treating cat allergic patient. + T cells in all allergic manifestations, however, largest numbers were detected upon stimulation with house dust mite & grass pollen extracts.…”
Section: Resultsmentioning
confidence: 98%
“…Serum specific IgE (sIgE) to crossreactive carbohydrate determinants (CCD) and raw peanut extract were also assessed. ALFA results for sIgE (colorimetric result units) were compared to ImmunoCAP 250 (expressed in kU A /L) and ImmunoCAP ISAC (expressed in ISU) sIgE data for the same serum samples from 19 peanut-allergic patients (9 boys) with a median age of 10 years (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). For semiquantitative comparison, we defined 7 classes for each method, based on the intensity of the sIgE signal.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent article has shown that dog saliva is an important source of dog allergens with four new allergens that are not normally present in the current dog extracts. Also the IgE binding proteins in saliva from different breeds of dog vary [3]. Patients often tell us that some breeds of dogs cause more allergic symptoms than others.…”
Section: Introductionmentioning
confidence: 99%